2007
DOI: 10.3171/jns-07/07/0068
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of blood flow in perforating arteries using fluorescein cerebral angiography during aneurysm surgery

Abstract: Because the fluorescein angiography procedure described here allows intraoperative confirmation of the patency of perforating arteries located deep inside the surgical field, it can be practically used for preventing unexpected cerebral infarction during aneurysm surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 25 publications
0
35
0
3
Order By: Relevance
“…DSA can also reveal the fate of a complex aneurysm following bypass surgery and/or trapping strategies (aneurysmal thrombosis, residual filling) [4]. Drawbacks are represented by its invasiveness, high costs, necessity of ionizing radiation, and prolonged operative time (15-60 min) [4][5][6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DSA can also reveal the fate of a complex aneurysm following bypass surgery and/or trapping strategies (aneurysmal thrombosis, residual filling) [4]. Drawbacks are represented by its invasiveness, high costs, necessity of ionizing radiation, and prolonged operative time (15-60 min) [4][5][6][7].…”
mentioning
confidence: 99%
“…It can be difficult to place the probe on the target vessel in a deep surgical field. Furthermore, even if the target vessel can be touched with the probe, it may detect flow from nearby vessels: in fact, the continuous Doppler wave method detects blood flow in a relative wide region [6].…”
mentioning
confidence: 99%
“…ICG and fluorescein are 2 unique fluorophores used successfully as surgical adjuncts in aneurysm surgery, and, based on their unique chemical properties, they provide distinct advantages and disadvantages. 9,11 At least 3 other groups of investigators have reported the drawbacks of ICG-VA related to its poor image quality in deep operative fields. [1][2][3]10 More specifically, these investigators found a higher incidence of discordance between ICG-VA and postoperative angiograms during ACoA aneurysm surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In vascular studies by Wrobel et al, 11 perforating medium and large arteries were visualized following aneurysmal clip ligation using fluorescein angiography. In 2007, Suzuki et al 9 reported on the development of a pencil-type probe with a light-emitting diode to allow fluorescein fluorescence interrogation of the arteries deep inside the surgical field. These authors reported excellent image quality and spatial resolution.…”
mentioning
confidence: 99%
“…This small dose is 15% of the dose previously used for neoplastic and vascular applications. 3,5,9,15,22,24 We chose this dose based on our previous experience. We had decreased fluorescein dosing gradually from 200 mg in 25 increments for the previous 10 patients who harbored brain aneurysms.…”
Section: Technique For Fluorescence Angiographymentioning
confidence: 99%